Actions of salvianolic acid A on CCl4-poisoned liver injury and fibrosis in rats - Hu Yi-Yang; Liu Ping; Liu Cheng; Xu Lie-Ming; Liu Cheng-Hai; Zhu Da-Yuan; Huang Mei-Fen (Acta Pharmacologica Sinica; Vol 18, No 5 (September 1997): Acta Pharmacologica Sinica, 2016)
AIM: To study the actions of salvianolic acid A (SA-A) on liver injury and liver fibrosis. METHODS: The liver fibrotic rat was made by i.p. injection of CCl4. The model rats were divided into 3 groups treated with SA-A, colchicine (Col), and Salvia miltiorrhiza Bunge (SMB), respectively. Six wk later the rat liver pathology was examined, type I and III collagen in the liver were examined by immunohistochemistical method. Also hydroxyproline (Hyd) and malondialdehyde (MDA) in the liver, alanine aminotransferase (AlaAT), aspartate aminotransferase (AspAT), and albumin (Alb) levels in the serum were measured. RESULTS: SA-A inhibited serum AlaAT and AspAT activities, decreased MDA and Hyd contents, alleviated liver fibrogenesis, protected deposition of type I and III collagen in liver matrix. The actions of SA-A on liver fibrosis were similar to those of Col and SMB, action of SA-A decreasing MDA was better than that of Col. CONCLUSION: SA-A has marked effects against liver injury and fibrosis, associated with its anti-lipid peroxidation actions.